Sonate pastorale pour le pianoforte par Louis van Beethoven. Oeuv. 28 ...; Soigneusement revue & corrigée ; metronomisée par J. Moscheles - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Moscheles, Ignaz, 1794-1870 (editor):::Contributor:::::::::::: (Germany; A. Cranz; Hamburg, 2022)
Early edition of the Piano Sonata no. 15 in D major, op. 28, published by A. Cranz in Hamburg. Issued in a decorative cover with collective title and statement "Nouvelle edition très correcte, métronomisée par I. Moscheles."